THE ROLE OF SUSTAINABILITY LEADERSHIP AND SCHOOL- COMMUNITY PARTNERSHIP ON ORGANIZATIONAL SUSTAINABILITY - Purbiyati, Yuliana Sri (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study examines the influence of sustainability leadership and school-community partnerships on organizational sustainability. This study also examines the influence of human resource competency on school-community partnerships. Data collection in this study used a survey with a questionnaire. The determination of the sample for this study follows the opinion of Mwenda et al. (2023), namely managing the target population using a census approach which means that all existing work units are research samples. This study is a study at the work unit level, so the sample determination uses a census approach, namely if the population is less than 200 units, all work units are samples (Israel, 1992). The research sample consisted of 20 work units of vice principals from five schools based on certain religions in Java. Hypothesis testing in this study used partial least squares structural equality modeling (PLS-SEM). The findings of this study are that there is a significant relationship between sustainability leadership and school-community partnerships with organizational sustainability and the influence of human resource competency on school-community partnerships. The practical implications of this research for principals and school administrators are that sustainability leadership and school-community partnerships build organizational sustainability and human resource competency builds school-community partnerships. In future research, the same thing can be studied in terms of indirect relationships, either through mediators or mediation.